IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING ANALYTICAL EXPOSITION THROUGH DEBATE TECHNIQUE - Nova Diana Simbolon and Siti Aisyah Ginting (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study attempts to improve students’ achievement in writing Analytical Expositionthrough Debate Technique. This study was conducted by using classroom actionresearch. The subject of the research was class XI IPA-1 SMAN 1 Pancur Batuconsisting of 36 students. The research was conducted in two cycles and consisted of sixmeetings. The instruments for collecting data were writing tests as the quantitative dataand diary notes, observation sheet, and interview sheet as qualitative data. Based on thewriting score, students’ scores kept improving in every test. In the first cycle test, themean of writing score was 61,67. In the second cycle test the mean of writing score was71,36. Based on diary notes, observation sheet and questionnaire sheet, it was found thatstudents were actively involved in writing process. The result of the research showedthat Debate Technique can improve students’ achievement in writing AnalyticalExposition.